PERANCANGAN SIGN SYSTEM KAMPUNG TENUN DI SUNGAI JAMBUA KABUPATEN SOLOK - TEGUH WAHYUNDRI. S, Dr. M. Nasrul Kamal, M.Sn., Riri Trinanda, S.Pd., M.P. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The purpose of this design is to design an informative sign system, have a visual appeal with the theme, a form of communication with a clear and effective approach so as to facilitate the target audience towards the location of the weaving craftsmen.The method used in designing this sign system is through the glass box approach, with the analysis of the data used is 5W + 1H (what, who, where, when, why, and how) to find a solution to the problem at hand.This design produced a draft sign system for weaving on the Jambua River in Solok Regency namely Identification Sign, Direction Sign, and information sign as the main media, and also supported by several other media, namely: posters, key chains, pins, t-shirts, stickers, and Paper bag, as supporting the main media and as a media campaign.Keywords: Sign system, house weaving, craft